PEMBENTUKAN KARAKTER RASA HORMAT DALAM PEMBELAJARAN TEMATIK SISWA KELAS III SD 7 HADIPOLO - Putri Sukrotin Ni’mah; Imaniar Purbasar; Deka Setiawan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article discusses the forms of character-building respect in students' thematic learning in class III of elementary school 7 Hadipolo. The main focus of this research is the teachers’ efforts to instill the character-building of respect in the students’ thematic learning in class III. The study described in this article uses a qualitative approach with a descriptive qualitative research method and students in class III as the research subject. The object of the study in this article is the students’ respect for character-building. The research used interviews, observation, and documentation as the technique of data collection. The results of the study indicated that the character-building of respect that teachers did in thematic learning such as creating a conducive atmosphere, habituation, integration in learning, modelling, and giving punishment. The character values of respect that students have were embedded and applied in thematic learning in class. Respect attitude and behaviour that students have included students always said greetings when meeting with teachers, were honest in doing assignments, were respectful and polite to teachers, were tolerant, and made friends circle with friends in different religions and others. Whilst the factors that influence the teacher in instilling the character of students’ respect was based on the family environment and the surrounding environment.